2020
DOI: 10.21873/anticanres.14706
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and CD11b+ Cell Influx Are Strongly Associated With Lymph Node Metastasis of Oral Cancer

Abstract: Background/Aim: Treatment failure in oral cancer is mainly caused by uncontrolled cervical lymph node (LN) metastasis. We previously reported that CD11b+ cells are recruited into tumor hypoxic areas following radiation, leading to re-vascularization and relapse. Since lymphatic vessel formation has similarities with vascular formation, we examined whether surgery induces hypoxia and stimulates lymphangiogenesis. Materials and Methods: The recruitment of CD11b+ cells and the formation of lymphatic vessels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Additionally, the recruited CD11b positive cells in hypoxia areas of the tumor have been reported to stimulate the lymphangiogenesis and lymph node metastasis in a glossectomy orthotopic mouse model of tongue cancer. 48 Similarly, our study also showed that the patients with an elevated NAR value pretreatment exhibited a high risk of regional recurrence. Moreover, peripheral neutrophils‐circulating tumor cells clusters have been reported to promote tumor progression in breast cancer.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, the recruited CD11b positive cells in hypoxia areas of the tumor have been reported to stimulate the lymphangiogenesis and lymph node metastasis in a glossectomy orthotopic mouse model of tongue cancer. 48 Similarly, our study also showed that the patients with an elevated NAR value pretreatment exhibited a high risk of regional recurrence. Moreover, peripheral neutrophils‐circulating tumor cells clusters have been reported to promote tumor progression in breast cancer.…”
Section: Discussionsupporting
confidence: 73%
“…This then reduces the survival rate. Additionally, the recruited CD11b positive cells in hypoxia areas of the tumor have been reported to stimulate the lymphangiogenesis and lymph node metastasis in a glossectomy orthotopic mouse model of tongue cancer 48. T A B L E 2…”
mentioning
confidence: 99%
“…The occurrence of LNM in oral cancer patients usually predicts a poor prognosis [ 20 ]. Evidence has shown that hypoxia might result in the infiltration of relevant cells, including immune cells, in cancer tissues, which facilitates angiogenesis and thus expedites cancer metastasis [ 21 ]. In addition, hypoxia can induce the expression of relevant genes, and then stimulate cells to undergo the EMT through factors such as FGF1 , thereby promoting angiogenesis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we confirmed the cell migration ability in vivo. We established an orthotopic xenograft tongue tumor model in a prior study 24 . In this study, we implanted the EP4-overexpressing HSC-3 cells expressing green fluorescent protein (GFP) and luciferase into the tongues of mice, and determined the number of lymph node metastases with a fluorescence microscope and an in vivo bioluminescence imaging system (IVIS).…”
Section: Resultsmentioning
confidence: 99%